A cross-sectional study of chronic liver disease patients complicating to hepatic osteodystrophy - P., Mohammed Jaleel; Devi, S. Bhagyabati; Reema, Ningthoukhongjam; Singh, Thangjam Gautam; P., Dhileeban Maharajan (International Journal of Advances in Medicine, 2020)
Background: Hepatic osteodystrophy encompasses the spectrum of metabolic bone diseases in chronic liver disease (CLD) patients. CLD causing changes in BMD is well known. Although BMD evaluation in CLD cirrhosis are recommended by societies of British and American gastroenterology ,very less number of literature exist from India and none from the North-eastern region of India. Aim of the study to determine the association and severity of bone mineral density changes in patients with CLD and to correlate it with different aetiologies and severity of CLD. Methods: This cross-sectional study which included 79 patients with CLD was conducted in RIMS, Manipur from September 2017 to August 2019. All CLD patients of age 18-60 years were included. DEXA scan and other related blood investigations were performed. Results: Chronic alcohol intake (56.9%), viral infection (20.3%) and mixed (17.7%) were the main aetiology of CLD in our study. Seventy three (92.4%) of the total 79 patients had low BMD (Osteopenia in 29 (36.7%) and osteoporosis in 44 (55.7%) patients). Osteoporosis was detected in 53.4% of alcohol related Cirrhosis, 25%of viral liver disease. Majority of the severe CLD patients (Child class C) had osteoporosis (70.6%) as compared to less severe groups (23.5% and 36.4% in class B and A respectively). Conclusions: CLD patients have high prevalence of osteoporosis. Severity of liver disease, alcoholic liver disease, serum calcium and vitamin D deficiency predisposes to osteoporosis in these patients. Hence early screening of BMD is necessary in CLD patients.